2020
DOI: 10.1007/s10266-020-00547-3
|View full text |Cite
|
Sign up to set email alerts
|

Composition’s effect of Origanum Syriacum essential oils in the antimicrobial activities for the treatment of denture stomatitis

Abstract: This research has several purposes: First to assess the bacterial and fungal minimum inhibitory concentration of Origanum Syriacum essential oil. Second to quantify its bactericidal and fungicidal minimal concentration against S. aureus , S. mutans , and C. albicans found in denture stomatitis. The third purpose is to look at the influence of three different soils (Annaya, Bhanin and Michrif) on the essential oils compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 52 publications
1
10
1
Order By: Relevance
“…Due to the proportion of chemical constituents found in the synthesis of all three essential oils, the disparity in MIC and MFC values can be attributable. The difference between this study's findings and other studies can be mainly due to the variations in the composition of each plant ecotype and the difference in the study design [23].…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Due to the proportion of chemical constituents found in the synthesis of all three essential oils, the disparity in MIC and MFC values can be attributable. The difference between this study's findings and other studies can be mainly due to the variations in the composition of each plant ecotype and the difference in the study design [23].…”
Section: Discussioncontrasting
confidence: 90%
“…Nonetheless, Shore A hardness value for the 28-day elevated value unquestionably correlated with the 24-hour Shore A hardness value for all the groups of essential oil, and this result is in agreement with studies conducted by Kim et al, [19]. In a study by Kim et al [19], "GC Reline Soft showed the mean durometer Shore A hardness of 50.13 ± 0.48 for 24 hours and 57.20 ± 0.28 for 28 days [23]." In the present study, there is a linear increase in mean hardness values in all groups from baseline, which are all significant (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Shamseddine and Chidiac (24) found that Origanum Syriacum have different antimicrobial efficiency against most strains related to DS with a higher efficiency associated to carvacrol content. Carvacrol is possibly one of the major components linked to Origanum Syriacum's anti-fungal effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 9 ] Recent studies have also proven its antioxidant effect, anticancer, antibacterial, antifungal, and anti-acetylcholine oxidant. [ 3 10 11 12 13 14 15 16 17 18 ] Efficacy against colon cancer and breast cancer was also confirmed. [ 19 ] These medicinal properties are because of its richness in carvacrol (it can be up to79.8% from the content of essential oils) and Thymol (it can be up to 83, 8%).…”
Section: Introductionmentioning
confidence: 90%